Le tracce del passato e l'impronta del presente Scritti in memoria di Giovanni Lilliu - Perra, Mauro; Cicilloni, Riccardo (Quaderni di Layers, 2018)
The great Scientist Giovanni Lilliu, as well as the most important archaeologist of the last century, was also a lively intellectual, attentive to numerous issues that also exuded archeology, themes strongly linked, however, to the culture and language of his beloved Sardinia. His wealth of interests, his love of complexity, is reflected in the present volume, in which various scholars, especially archaeologists but not only, wanted not only to remember the Master, but also to take up the themes treated by him, often deepening them in the light of the new discoveries and research.